Predictors of chronic kidney disease in type 2 diabetes: A longitudinal study from the AMD Annals initiative. Issue 27 (July 2016) - De Cosmo, Salvatore; Viazzi, Francesca; Pacilli, Antonio; Giorda, Carlo; Ceriello, Antonio; Gentile, Sandro; Russo, Giuseppina; Rossi, Maria C.; Nicolucci, Antonio; Guida, Pietro; Pontremoli, Roberto; ,
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The identification of clinical predictors for the development of chronic kidney disease is a critical issue in the management of patients with type 2 diabetes mellitus. We evaluated 27, 029 patients with type 2 diabetes mellitus and estimated glomerular filtration rate (eGFR) ≥60 mL/min/1.73 m 2 and normoalbuminuria from the database of the Italian Association of Clinical Diabetologists network. Primary outcomes were eGFR <60 mL/min/1.73 m 2 and normoalbuminuria; albuminuria and eGFR ≥60 mL/min/1.73 m 2 ; and eGFR <60 mL/min/1.73 m 2 and albuminuria. Secondary outcomes were eGFR <60 mL/min/1.73 m 2 and albuminuria. Measurements: eGFR from serum creatinine by chronic kidney disease epidemiology collaboration equation (CKD-EPI), urinary albumin excretion, HbA1c, triglycerides, high-density lipoprotein cholesterol (HDL-c) and low-density lipoprotein cholesterol (LDL-c), blood pressure, and body mass index. Over a 4-year period, 33.2% of patients (n = 8973) developed chronic kidney disease, 10.3% (n = 2788) showed a decline in eGFR <60 mL/min/1.73 m 2, 18.4% (n = 4978) developed albuminuria, and 4.5% (n = 1207) developed both features. Relative risk ratios (RRRs) for age (1.37, P  < 0.001 by 5 years), sex (0.77, P  < 0.001 for being male), body mass index (1.03, P  < 0.001 by 1 kg/m 2 ), triglycerides (1.02, P  < 0.001 by 10 mg/dL), and LDL-c (0.97, P = 0.004 by 10 mg/dL) were independently related to the onset of eGFR reduction. Age (1.08, P  < 0.001 by 5 years), sex (1.36, P  < 0.001 for being male), body mass index (1.02, P  < 0.001 by 1 kg/m 2 ), triglycerides (1.01, P = 0.02 by 10 mg/dL), HDL-c, and LDL-c (0.97, P = 0.008 and 0.99, P = 0.003 by 5 and 10 mg/dL, respectively) were related to the onset of albuminuria. HbA1c and the intensity of antihypertensive treatment showed a weaker association with renal outcome. Reduction in eGFR and albuminuria showed distinct sets of risk factors, suggesting that different mechanisms are involved in the development of these 2 components of diabetic kidney disease.